2023
DOI: 10.1021/acs.chemmater.2c03831
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of La0.75Sr0.25CrO3 Thin Films for p-Type Transparent Conducting Electrodes

Abstract: The imperative need for highly performant and stable p-type transparent electrodes based on abundant metals is stimulating the research on perovskite oxide thin films. Moreover, exploring the preparation of these materials with the use of cost-efficient and scalable solution-based techniques is a promising approach to extract their full potential. Herein, we present the design of a chemical route, based on metal nitrate precursors, for the preparation of pure phase La0.75Sr0.25CrO3 (LSCO) thin films to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…In addition, from the strain maps in Figure d, it is observed that the BFO film exhibits inhomogeneous lattice deformations likely due to the numerous nucleation of structural defects that locally relax the BFO lattice. In fact, CSD tends to promote the formation of structural defects within the epitaxial thin film, as previously reported in other complex oxides. ,, A more detailed analysis of these local deformations in the BFO layer by means of atomically resolved STEM images is presented in Figure S4.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…In addition, from the strain maps in Figure d, it is observed that the BFO film exhibits inhomogeneous lattice deformations likely due to the numerous nucleation of structural defects that locally relax the BFO lattice. In fact, CSD tends to promote the formation of structural defects within the epitaxial thin film, as previously reported in other complex oxides. ,, A more detailed analysis of these local deformations in the BFO layer by means of atomically resolved STEM images is presented in Figure S4.…”
Section: Resultssupporting
confidence: 67%
“…Further XRD structural analysis from this heterostructure identifies that the LSMO film is partially strained (+0.3%), whereas the BFO is fully relaxed with a = 3.96 Å, matching the bulk value . This is not surprising considering that CSD films with similar thickness tend to grow fully relaxed through the formation of structural defects. , Cross-section STEM reveals the growth of three discrete layers in which BFO presents few Fe-rich secondary phases, ,, Figure b. Image magnification at the BFO/LSMO interface shows the atomic structure of both phases, corroborating their epitaxial relationship with an atomically sharp interface, Figure c.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…We performed a thorough study on the influence of the solution chemistry based on metal nitrates to ultimately obtain epitaxial and reasonably smooth films on (001) STO and (001) LaAlO 3 (LAO) substrates. 93 The optimal formulation appeared to be nitrate precursors in 2-methoxyethanol, acetic acid and diethanolamine, processed in air which results in dense, epitaxial and slightly strained films. These LSCO films display 67% optical transparency in the visible spectrum being as good as those reported for some of the most promising state of the art TCOs.…”
Section: Complex Oxides On Rigid Substratesmentioning
confidence: 99%